Seasoldier's Brand Activation Strategy in the Penta Helix Model (Spreading Environmentally Friendly Viruses at the Deep Extreme Indonesia Event) - Septiana, Winda; Angelita, Gloria (Jurnal Mahardika Adiwidia, 2023)
Now many people are competing to do good for the environment, this positive thing is in the spotlight in the eyes of the world, namely regarding plastic waste. There are many laws and government regulations regarding waste, with retailers no longer providing single-use shopping bags and the effect of the Covid 19 pandemic has reduced the problem of waste a little. The Seasoldier Community, founded by Nadine Chandrawinata and Dinni Setianingrum, has dared to carry out a movement with various actions to spread environmentally friendly viruses to the community. One of them has been done at Deep Extream Indonesia. This research method uses a qualitative approach and the type of research is descriptive. This research aims to analyze the Brand Activation Strategy in the Penta Helix Model by spreading environmentally friendly viruses at the Deep Extream Indonesia 2023 event. This research raises a sense of care and awareness so that every individual lives by keeping the environment clean, healthy and becomes an inherent culture. Cleaning up trash is no longer an obstacle for society but a reward.Keywords: Brand Activation, Penta Helix Model, Environmentally Friendly Virus, Seasoldier, Deep Extream Indonesia.